Influence of sulfate reducing bacteria on the cupronickel corrosion. Issue 6 (28th October 2014) - Kecheng, Liu; Xia, Liu; Xiao, Long; Jiaqiang, Wei; Mengsha, Hu; Baiqing, Zhou
Abstract : Purpose: – The purpose of this study is to explore the influence of the sulfate reducing bacteria (SRB) on the corrosion of cupronickel. Design/methodology/approach: – Tests monitoring the change in free corrosion potential, linear polarization resistance and electrochemical impedance spectroscopy and examination using the scanning electron microscope and energy spectrum analysis were used to investigate the corrosion behavior of cupronickel in blank medium and in media inoculated with SRB to explore the influence of the SRB on the corrosion behavior of cupronickel alloy. Findings: – The results show that SRB can destroy the surface oxide film of cupronickel and significantly reduce the free corrosion potential and polarization resistance of the cupronickel, causing the cupronickel to corrode significantly. Originality/value: – SRB are widely found in the water supply system and is one of the important factors inducing microbial corrosion. This paper verified that SRB promote cupronickel corrosion and explored the influence and mechanism of attack.